A new species of the spider genus Pomboa Huber (Araneae: Pholcidae) from Colombia - Valdez-Mondragón, Alejandro (Zootaxa, 2012)
The spider genus Pomboa Huber, 2000 (Pholcidae: Modisiminae), includes three species, all from Colombia: P. cali Huber; P. pallida Huber; and P. quindio Huber (Platnick, 2012). The spiders are medium-size (1.7-3.3 mm), and show only slight sexual dimorphism (Huber, 2000). The monophyly of the genus is supported by the widely curved procursus. In P. pallida and P. quindio, the procursus bears a dorsoproximal spine that is accompanied by membranous fringes (Huber, 2000). The relationships of the genus are not yet clear (Huber, 2011). In this paper a fourth species of Pomboa is described.